141 Phase I Trial of Genetically Modified Hematopoietic Progenitor Cells Facilitate Bone Marrow Chemoprotection and Enabling TMZ/O6BG Dose Escalation Resulting in Improved Survival. (August 2016) - Sloan, Andrew E.; Fung, Hua; Reese, Jane; Rogers, Lisa R.; Murphay, Christopher; Lazrus, Hillard; Dropulic, Boro; Gerson, Stan L.
Abstract : INTRODUCTION: Glioblastoma (GBM) is the most common malignant brain tumor with a median survival of 15 months despite surgery and aggressive radiochemotherapy. The most important mechanism of temozolomide (TMZ) resistance is the O 6 -methylguanine-DNA methyltransferase (MGMT) gene that repairs temozolomide-induced DNA methylation. The MGMT inhibitor O 6 -benzylguanine (BG) has demonstrated efficacy in depleting MGMT and maximizing tumor response in early-phase clinical trials. However, because MGMT expression is also low in hematopoietic cells, this has resulted in unacceptable bone marrow toxicity, and this approach has been abandoned. We hypothesized that chemoprotection of hematopoietic progenitor cells (HPC) with an MGMT mutant (MGMT-P140K) characterized by normal methyltransferase activity coupled with low affinity for BG, would maximize antitumor response while enabling patients to tolerate TMZ and BG dose escalation with minimal toxicity. We thus performed a phase I trial to test this hypothesis. METHODS: We treated 10 consecutive newly diagnosed GBM patients with standard surgery and radiation, followed by transplantation with autologous CD34 + hematopoietic progenitor cells engineered to express MGMT-P140K using a lentiviral vector using 3 different arms. To assess chemoprotection, patients' blood counts and transgene marking were monitored during the treatment as was tumor growth and survival. RESULTS: The viral transduction rates were 2.5% to 75% and were clearly improved in the third arm with intrapatient dose escalation. P140K-MGMT gene markings in peripheral blood and bone marrow cells increased 3- to 26-fold with only mild (Grade 2-3) myelosuppression consistent with chemoselection and chemoprotection as hypothesized. Survival ranged from 20 to 36 months, which exceeded their recursive partitioning analysis-predicted survival by 1.9- to 3.2-fold suggesting clinical benefit (mean 2.0). Viral insertion site analysis failed to demonstrate clonal dominance. CONCLUSION: These preliminary results demonstrate that this chemoprotection strategy is tolerable, safe, and facilitates TMZ and BG dose escalation resulting in increased survival. A phase II study is ongoing.